2016
DOI: 10.1007/s00436-016-5149-4
|View full text |Cite
|
Sign up to set email alerts
|

Fresh fruits, vegetables and mushrooms as transmission vehicles for Echinococcus multilocularis in highly endemic areas of Poland: reply to concerns

Abstract: Echinococcus multilocularis is a tapeworm that may cause alveolar echinococcosis (AE), one of the most dangerous parasitic zoonoses. As in the case of other foodborne diseases, unwashed fruits and vegetables, contaminated with dispersed forms of E. multilocularis, may serve as an important transmission route for this parasite. In this article, we reply to the incorrect interpretation of results of our study concerning the detection of E. multilocularis DNA in fresh fruit, vegetable and mushroom samples collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 22 publications
0
6
0
2
Order By: Relevance
“…multilocularis and E. granulosus s.l. is still ongoing (Federer et al., ; Lass et al., ; Robertson et al., ). Two recent reviews and meta‐analyses suggested that the chance of AE and CE transmission through the ingestion of food and water contaminated with E .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…multilocularis and E. granulosus s.l. is still ongoing (Federer et al., ; Lass et al., ; Robertson et al., ). Two recent reviews and meta‐analyses suggested that the chance of AE and CE transmission through the ingestion of food and water contaminated with E .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the debate on the importance of unwashed contaminated fresh fruit, vegetables and mushrooms in the transmission of E. multilocularis and E. granulosus s.l. is still ongoing (Federer et al, 2016;Lass et al, 2016;Robertson et al, 2016). Two recent reviews and meta-analyses suggested that the chance of AE and CE transmission through the ingestion of food and water contaminated with E. multilocularis and E. granulosus eggs does exist, but potential risk factors associated with foodborne and waterborne transmission do not significantly increase the risk of infection to humans Conraths et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…However, they do serve to provide a general view of the contamination risk in kitchen gardens. Indeed, as discussed by Lass et al [ 31 ], the detection of parasite DNA in faeces is evidence of their presence in the environment and indicates a potential risk for humans, even though this alone does not allow the level of risk to be determined – this would require investigating the viability of the infective stage of the parasites and the parasite burden per faeces. In line with Conraths and Deplazes [ 6 ], we consider that data from faeces collected in the environment has the advantage of yielding more relevant information for preventing foodborne parasite transmission than investigating prevalence in definitive host populations, since humans run a much higher risk of contamination from contact with the environment than from contact with definitive hosts.…”
Section: Discussionmentioning
confidence: 99%
“…Robertson et al (2016) also suggest that the high number of environmental samples positive for E. multilocularis is unreliable because of the low number of human alveolar echinococcus (AE) cases. Lass et al (2016) argued that their results are credible because of the focal distribution of highly infected foxes, and notification of human cases, and the relative resistance of humans to this disease. However, it is also necessary to further consider the latent period between infection and clinical disease.…”
Section: Fresh Fruits Vegetables and Mushrooms As Transmission Vehicmentioning
confidence: 99%
“…Thus, in contrasts to the contention by Robertson et al (2016) raspberries would not need to be at ground level to be contaminated with Echinococcus eggs if this mechanism is invoked, particularly since samples taken by Lass et al (2015) were from areas of high fox density. Although Lass et al, (2016) were aware of a problem regarding the mechanism of transmission to hanging fruit and hence took raspberries from a low level, it would be possible for insects to contaminate the fruits high up on the raspberry bushes.…”
Section: Fresh Fruits Vegetables and Mushrooms As Transmission Vehicmentioning
confidence: 99%